Controlling weeds in Pacific Northwest pulse crops. Issue 2 (24th May 2016) - Campbell, Joan
Abstract : Washington and Idaho account for 71% of the chickpea acreage in the U.S. while producing about 15% of the pea and 18% of the lentil crops. One of the most challenging aspects of producing these pulse crops in this region is weed control. Earn 0.5 CEU in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/764 .